Effects, experiences, and impact of stigma on patients with bipolar disorder - Mileva VR (Dove Medical Press, 2013)
Viktoria R Mileva,1 Gustavo H Vázquez,2 Roumen Milev31Psychology, School of Natural Sciences, University of Stirling, Stirling, UK; 2Department of Neurosciences, University of Palermo, Buenos Aires, Argentina; 3Department of Psychiatry, Queen's University, Kingston, ON, CanadaBackground: Many people with mental illness experience stigma that has impacted their lives. In this study, we validated the Inventory of Stigmatizing Experiences (ISE) as a tool to help quantify the stigma experienced by patients with bipolar disorder and its impact on their lives. The ISE has two components, ie, the Stigma Experiences Scale (SES) and the Stigma Impact Scale (SIS), which were administered to a population of Argentinean patients with bipolar disorder. We characterized the differences between these two populations using the SES and SIS. Finally, we compared SES and SIS scores with those in a population of Canadian patients with bipolar disorder.Methods: The SES and SIS scales were administered to tertiary care patients with bipolar I and II disorder in Argentina (n = 178) and Canada (n = 214).Results: In this study, we validated both SES (Kuder–Richardson coefficient of reliability, 0.78) and SIS (Cronbach's alpha, 0.91) scales in a population of Argentinean patients with bipolar disorder. There were no significant differences in stigma between patients with bipolar I or II disorder on SES or SIS. However, over 50% of all respondents believed that the average person is afraid of those with mental illnesses, that stigma associated with mental illness has affected their quality of life, and that their self-esteem has suffered due to stigma. In comparison with the Canadian population, Argentinean participants scored lower on both the SES and SIS, which may be due to cultural differences or to differences in population characteristics.Conclusion: Stigma associated with mental illness is serious and pervasive. If we are to find successful strategies to mitigate stigma, it is first important to understand how patients perceive such stigma. The ISE is a valuable tool which allows us to do this with high reliability among cultures.Keywords: stigma, bipolar disorder, scale, experiences, impact, Inventory of Stigmatizing Experiences